السياسة الخارجية للإتحاد الاوربي في نظريات العلاقات الدولية – حالة تطبيقية - طلال مقلد, حسين (revue mofakir, 2018)
The European Union (EU) has a foreign policy, but this policy lacks strategy and goals. It is connected with many other players, member state populations, governments and EU institutions. In my research, I will address two major questions. The first question is related to the best theory of international relations which explains the EU foreign policy. The second one I will ask, is the membership in EU ends the national foreign policies of EU member states in single EU foreign policy ? I will concentrate on some examples of decision making in the aspect of foreign policy.